Creative skills acquired by university students through curricula - Salwa Al Majali, Hani Jarrah, (Opción, 2019)
This study aimed to identify the creative skills acquired by university students through the curricula. The present study is based on the analytical descriptive approach in order to identify the creative skills acquired by the students of Al Ain University for Science and Technology through the curriculum. The results showed that the students' assessment of the role of the curriculum in the development of creative skills among university students is average. In conclusion, the results indicated that there are no statistically significant differences in all fields of creative skills due to the variables of gender, academic year and university specialization.